The Social Entrepreneurship Intention on Islamic Boarding School in Garut Regency - Anisa, Muni; Kurjono, Kurjono; Yusof, Rohaila binti (Islamic Research, 2024)
The purpose of this paper is to examine the social entrepreneurship intentions of Islamic boarding school students in Garut Regency, as well as to analyze the moderation of the TPB component's creativity. The Grand Theory used is Ajzen's Theory of Planned Behavior. There are 260 students in Islamic boarding schools in the city of Garut. Collect data by questionnaire, five-point numerical type scale. Meanwhile, data analysis using Regression Analysis results identified that the TPB component consisting of Attitudes towards behavior, Subjective Norms and Perceived Behavioral Control had a positive and significant effect on social entrepreneurship intentions, while creativity did not moderate the effect of entrepreneurial attitudes on social entrepreneurship intentions. The limitation of this research lies in the number of samples and students in Garut Regency. It is suggested to predict social entrepreneurship intentions in Islamic boarding school students in Garut district and examine variables other than TPB and creativity components.